Modern Industrial Services A Cookbook for Design, Delivery, and Management - West, Shaun; Gaiardelli, Paolo; Saccani, Nicola; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book is an outcome of several years of research, practice, and teaching experience of the authors on the challenges that underpin the successful switch to services for manufacturing firms. Ideal for a student as well as a practitioner, the book describes the industrial services ecosystem, the barriers and challenges, and a roadmap for building service excellence. Curated cases are used to describe the current approaches in practice to overcome the barriers. The book also provides several tools, each with a short introduction, that the authors have used successfully in projects to help overcome the servitization barriers. Many of these tools are from management, design thinking, or service design. The service excellence roadmap is based on the development methodology and helps current and future business leaders to create their own individual roadmaps.
1. Understanding the Barriers That Slow Firms Shifting from Products to Services -- 2. Overcoming the Barriers to Service Excellence -- 3. Methods and Tools for Overcoming the Barriers to Servitization and Service Excellence.
Keywords: Service industries; Business information services; Production management; Services; IT in Business; Operations Management